Faktor Psikologis Yang Mempengaruhi Kualitas Hidup Lansia: Studi Tentang Depresi, Kecemasan, Kualitas Tidur dan Ide Bunuh Diri di Panti Sosial - Delvi Kurniani; Kusharisupeni Kusharisupeni; Asyifa Robiatul Adawiyah (LPPM Universitas Respati Indonesia, 2026)
Background: The elderly are a vulnerable group facing physical, psychological, and social changes that can trigger a decline in quality of life. Although various studies have explored the well-being of older adults, research that simultaneously integrates suicidal ideation and sleep quality within the nursing home setting remains limited in Indonesia. Objective: This study aims to analyze the relationship between psychological factors (depression, anxiety, sleep quality, and suicidal ideation) and the quality of life of elderly residents in social homes, as well as to identify the most dominant psychological factor. Methods: This quantitative study utilized a cross-sectional design. The sample consisted of 145 elderly residents at Panti Sosial Tresna Werdha Budi Mulia 2, selected through total sampling. Instruments used included the GDS, GAD-7, PSQI, WHOQOL-Old, and SSI questionnaires. Data were analyzed using Chi-Square tests and multiple logistic regression. Results: Bivariate analysis showed that depression (p < 0.001), anxiety (p < 0.001), and sleep quality (p = 0.041) had a significant relationship with quality of life. Meanwhile, suicidal ideation showed no significant correlation (p = 0.969). Multivariate analysis revealed that anxiety was the dominant factor influencing the quality of life of the elderly (OR = 3.489; 95% CI: 1.576–7.724). Conclusion: Depression, anxiety, and sleep quality are significantly related to the quality of life of the elderly, with anxiety emerging as the dominant factor. Early detection efforts and psychosocial interventions must be enhanced in social homes to improve the overall well-being of elderly residents